2007
DOI: 10.1681/asn.2006101164
|View full text |Cite
|
Sign up to set email alerts
|

High NPHP1 and NPHP6 Mutation Rate in Patients with Joubert Syndrome and Nephronophthisis

Abstract: Joubert syndrome (JS) is an autosomal recessive disorder that is described in patients with cerebellar ataxia, mental retardation, hypotonia, and neonatal respiratory dysregulation. Kidney involvement (nephronophthisis or cystic renal dysplasia) is associated with JS in one fourth of known cases. Mutations in three genes-AHI1, NPHP1, and NPHP6-have been identified in patients with JS. However, because NPHP1 mutations usually cause isolated nephronophthisis, the factors that predispose to the development of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 42 publications
3
158
1
Order By: Relevance
“…Here we showed that, in mouse models of 2 important syndromes associated with great vessel defects, Chd7 and Tbx1 were in epistasis. Although epistasis between different genes mutated in the same human birth defect syndrome has been reported in a number of instances (47)(48)(49), interaction between genes haploinsufficient in distinct syndromes is rarer (50). In addition, both these genes were separately required to be expressed at biallelic levels in the embryonic pharyngeal ectoderm, emphasizing the importance of this epithelial tissue in PAA morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Here we showed that, in mouse models of 2 important syndromes associated with great vessel defects, Chd7 and Tbx1 were in epistasis. Although epistasis between different genes mutated in the same human birth defect syndrome has been reported in a number of instances (47)(48)(49), interaction between genes haploinsufficient in distinct syndromes is rarer (50). In addition, both these genes were separately required to be expressed at biallelic levels in the embryonic pharyngeal ectoderm, emphasizing the importance of this epithelial tissue in PAA morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, a potential epistatic effect of NPHP6 and AHI1 mutations in patients with Joubert syndrome and NPHP1 mutations was recently described. 22 We therefore examined whether oligogenic inheritance would also be present in NPHP. Here we present evidence for oligogenicity in NPHP1 through 4 by detecting two mutations in one of the NPHP genes in combination with a third mutation in another NPHP gene in six different families with NPHP (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Such an overlap is not unique to BBS within the ciliopathy disease group, where both the quality and quantity of alleles can impact pleiotropy and severity. Hypomorphic mutations in NPHP3 cause NPH, whereas null mutations in the same gene cause MKS (39); meanwhile the presence of bona fide pathogenic mutations at two NPHP loci has also been described (40), and these have been postulated to modulate the expressivity of the disease phenotype (41).…”
Section: Bbs As a Model Ciliopathymentioning
confidence: 99%